Original paperEarly outcomes of transcatheter aortic valve replacement in patients with severe aortic stenosis: single center experience - Bozkurt, Engin; Keleş, Telat; Durmaz, Tahir; Akçay, Murat; Sari, Cenk; Ayhan, Hüseyin; Bayram, Nihal Akar; Aslan, Abdullah Nabi; Baştug, Serdal; Bilen, Emine (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Introduction: Transcatheter aortic valve implantation is a promising alternative to high risk surgical aortic valve replacement.The procedure is mainly indicated in patients with severe symptomatic aortic stenosis who cannot undergo surgery or who are at very high surgical risk. Aim: Description early results of our single-center experience with balloon expandable aortic valve implantation. Material and methods : Between July 2011 and August 2012 , we screened in total 75 consecutive patients with severe aortic stenosis and high risk for surgery. Twenty-one of them were found ineligible for transcatheter aortic valve implantation (TAVI) because of various reasons, and finally we treated a total of 54 patients with symptomatic severe aortic stenosis (AS) who could not be treated by open heart surgery (inoperable) because of high-risk criteria. The average age of the patients was 77.4 ±7.1; 27.8% were male and 72.2% were female. The number of patients in NYHA class II was 7 while the number of patients in class III and class IV was 47. Results: The average mortality score of patients according to the STS scoring system was 8.5%. Pre-implantation mean and maximal aortic valve gradients were measured as 53.2 ±14.1 mm Hg and 85.5 ±18.9 mm Hg, respectively. Post-implantation mean and maximal aortic valve gradients were 9.0 ±3.0 and 18.2 ±5.6, respectively (p < 0.0001). The left ventricular ejection fraction was calculated as 54.7 ±14.4% before the operation and 58.0 ±11.1% after the operation (p < 0.0001). The duration of discharge after the operation was 5.29 days, and a statistically significant correlation between the duration of discharge after the operation and STS was found (r = 0385, p = 0.004). Conclusions : We consider that with decreasing cost and increasing treatment experience, TAVI will be used more frequently in broader indications. Our experience with TAVI using the Edwards-Sapien XT (Edwards Lifesciences, Irvine, CA) devices suggests that this is an effective and relatively safe procedure for the treatment of severe aortic stenosis in suitable patients.